Optimization of in vitro sterilization protocol for obtaining contamination-free cultures of Tilia platyphyllos - VAHIDEH PAYAMNOUR; KAMAL GHASEMI BEZDI; MOSTAFA MEHRDAD; AKRAM AHMADI (Smujo International, 2014)
Abstract. Payamnour V, Ghasemi Bezdi K, Mehrdad M, Ahmadi A. 2014. Optimization of in vitro sterilization protocol for obtaining contamination free cultures of Tilia platyphyllos. Nusantara Bioscience 6: 7-12. Tilia platyphyllos is one of threatened species of Caspian forests. Tissue culture techniques are applied for culture, regeneration and genetic resources preservation. Utilizing an accurate sterilization procedure is important to reduce the cost, time and energy. The aim of this present study was to provide optimization of in vitro sterilization protocol to obtain contamination-free cultures of T. platyphyllos. Explants were collected randomly from the best individuals of T. platyphyllos, which were located in Tooskestan forest of Gorgan, Iran. Results revealed that the optimum protocol for sterilization was when explants were exposed in pre-sterilizing solution of 600 mg L-1 ascorbic acid, 4 g L-1 captan fungicide and 5% commercial sodium hypochlorite (NaOCl) solution (5% Cl activated) for 20 minutes and then explants were exposed in sterilizing solution containing 600 mg L-1 ascorbic acid and 10% sodium hypochlorite.